Simulation of Gaussian Pulses Propagation Through Single Mode Optical Fiber Using MATLAB - Taha, Salah Al–Deen; Shellal, Mehdi; Kadhim, Ahmed (Iraqi Journal of Science, 2023)
Computer-aided modeling and simulation software programs are essential toolsto predict how an optical communication component, link, or network will functionand perform. This paper aims to investigate the various effects on pulsespropagation in optical transmission systems utilizing the MATLAB program.Dispersion and Attenuation effects are explored. The simulation of Gaussian pulsespropagation through single mode optical fiber, simplifies the design of opticalcommunication system and make the design process more efficient, less expensive,and faster.